Bacterial profile of urinary tract infection and antimicrobial susceptibility pattern among pregnant women attending at Antenatal Clinic in Dil Chora Referral Hospital, Dire Dawa, Eastern Ethiopia - Derese B; Kedir H; Teklemariam Z; Weldegebreal F; Balakrishnan S (Dove Medical Press, 2016)
Behailu Derese,1 Haji Kedir,2 Zelalem Teklemariam,3 Fitsum Weldegebreal,3 Senthilkumar Balakrishnan4 1Department of Medical Laboratory, Dil Chora Referral Hospital, Dire Dawa, 2Department of Public Health, 3Department of Medical Laboratory Sciences, 4Department of Medical Microbiology, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia Purpose: The aim of this study was to determine the bacterial profile of urinary tract infection (UTI) and antimicrobial susceptibility pattern among pregnant women attending at antenatal clinic in Dil Chora Referral Hospital, Dire Dawa, Eastern Ethiopia.Patients and methods: An institutional-based cross-sectional study was conducted from February 18, 2015 to March 25, 2015. Clean-catch midstream urine specimens were collected from 186 pregnant women using sterile containers. Then, culture and antimicrobial susceptibility tests were performed by standard disk diffusion method. Patient information was obtained using pretested structured questionnaire. Data were entered and cleaned using EpiData Version 3 and then exported to Statistical Package for Social Science (Version 16) for further analysis.Results: The prevalence of significant bacteriuria was 14%. Gram-negative bacteria were more prevalent (73%). Escherichia coli (34.6%), coagulase-negative staphylococci (19.2%), Pseudomonas aeruginosa (15.4%), and Klebsiella spp. (11.5%) were common bacterial isolates, where most of them were resistant against ampicillin, amoxicillin, tetracycline, trimethoprim–sulfamethoxazole, and chloramphenicol. Multidrug resistance (resistance in ≥2 drugs) was seen in 100% of the isolated bacteria. A majority of the bacterial isolates were sensitive to ciprofloxacin, ceftriaxone, erythromycin, and gentamicin.Conclusion: This study found a number of bacterial isolates with very high resistance to the commonly prescribed drugs from pregnant women with and without symptoms of UTI. Therefore, the early routine detection of causative agents of UTI and determining their drug susceptibility pattern are important for pregnant women to avoid complications in mother and fetus. Ciprofloxacin, ceftriaxone, gentamicin, and erythromycin can be used with great care for the empirical treatment of UTI. Keywords: pregnant, urinary tract infections, multidrug resistant, antenatal, Dil Chora, Dire Dawa